Delivery of siRNA using siRNA/cationic vector complexes encapsulated in dendrimer-like polymeric DNAs. Issue 41 (7th May 2015) - El-Mahdy, Ahmed F. M.; Shibata, Takayuki; Kabashima, Tsutomu; Zhu, Qinchang; Kai, Masaaki
<x xml:space="preserve">Abstract</x> A safe and efficient siRNA delivery system based on the electrostatic encapsulation of binary complexes of siRNA/cationic vector with dendrimer-like polymeric DNAs (YY-DNAs) was developed.